Every Forester a Timber Owner - Vitas, George (Indian Forester, 1947)
The author points outs that the profession has much to gain through every forester becoming a timberland owner. He rightly points out that the aggregate influence of such ownership would have tremendous. Weight with all forest landowners and with the public. He believe it would also prove a good investment provided arrangemts were worked out for others to take care of properties should the owner be transferred.